Planar and Nanostructured n‐Si/Metal‐Oxide/WO3/BiVO4 Monolithic Tandem Devices for Unassisted Solar Water Splitting. Issue 2 (27th October 2020) - Ahmet, Ibbi Y.; Berglund, Sean; Chemseddine, Abdelkrim; Bogdanoff, Peter; Präg, Raphael F.; Abdi, Fatwa F.; van de Krol, Roel
Abstract : A series of planar and nanostructured core‐shell photoanodes composed of n‐Si/SiO x /TiO2 /WO3 /BiVO4 heterojunctions are fabricated by chemical deposition methods. Aerosol‐assisted chemical vapor deposition (AA‐CVD) is utilized for the large area production of planar SnO2 and TiO2 thin films and compact WO3 nanorods, with the subsequent formation of WO3 /BiVO4 core‐shell nanostructures via solution deposition. Optimized monolithic dual photoanodes consisting of n‐Si/SiO x /TiO2 /WO3 /BiVO4 /Fe(Ni)OOH and a Pt cathode as the hydrogen evolution catalyst, provide a combined photo‐voltage capable of unassisted solar water splitting with a maximum photocurrent density of 0.3 mA cm −2 in 1.0 m KBi pH 9.3 buffer solution under solar simulated AM 1.5 G illumination. An average faradaic efficiency of ≈98% is confirmed by operando differential electrochemical mass spectroscopy (DEMS) for H2 production. Solid‐state J–V measurements of the individual n‐Si/SiO x /MO (MO = WO3, BiVO4, TiO2, or SnO2 ) interfaces in the dark and under illumination provide valuable insights into the unfavorable electrical properties at n‐Si/SiO x /WO3 or n‐Si/SiO x /BiVO4 junctions. The insertion of metal oxide buffer layers, such as SnO2 and TiO2, can mitigate surface recombination at the junctions between n‐Si/SiO x and WO3 or BiVO4 and strongly enhances the overall photovoltage. Abstract : Monolithic tandem nanostructured photoanodes based on n‐Si and coreshell WO3 /BiVO4 dual absorber layers are fabricated from scalable solution deposition processes. Junction engineering leading to enhanced interfacial properties enables unassisted solar water splitting. Differential electrochemical mass spectrometry is used as an operando technique to assess solar‐to‐hydrogen efficiencies. Solid‐state analysis of n‐Si/SiO x /metal oxide heterostructures provides valuable insights into heterojunction properties.